Nanoosciladores atomísticos de nanotubos de Carbono e de Nitreto de Boro - Garcez, Karl Marx Silva (2007)
The Nanotechnology quickly advances to the development of new nanodevices. One of most important in the electronics is clocks that they synchronize the functioning of diverse devices in a determined circuit. In this work we study the development of nanooscillators based upon Carbon nanotubes and Boron-Nitride nanotubes. The atom that oscillates in the interior of each tube is the Neon atom under various temperature conditions and for different nanotubes lengths. The results indicate oscillation stability in a large range of temperatures, what it could mean its potential construction and application as a new device for nanoelectronics.